Návrh marketingového mixu ve vybraném podniku - Růžičková, Žaneta (Vysoké učení technické v Brně. Fakulta podnikatelská, 2022)
Diplomová práce se zabývá návrhem marketingového mixu pro vybraný podnik. Diplomová práce je rozdělena na 3 části. První část je teoretická, kde jsou popsána teoretická východiska. V této části je popsán podnik obecně, jeho formy a funkce a marketingový mix podniku. Dále jsou navrženy výzkumné metody marketingového mixu. Na základě části teoretické a navržených výzkumných metod byly provedeny analýzy a kvalitativní výzkum podniku a jeho marketingového mixu. V třetí části diplomové práce jsou jednotlivé návrhy na zlepšení marketingového mixu podniku.

The diploma thesis is a proposal of a marketing mix for a selected company. It is divided into 3 parts. The first part is theoretical, where the theoretical background is described. This section describes the company, in general its functions and marketing mix of the company. Research is based on theoretical part. There are propose research methods, analysis and qualitative research marketing mix of the chosen company. In the third part of the thesis are individual suggestions for improving the marketing mix of the company.
Marketing Mix Proposal in Selected Company
Keywords: Marketing; marketingový mix; analýza obecného okolí; SWOT analýza; Porterův model pěti konkurenčních sil; model CANVAS; návrh marketingového mixu; spolupráce; veletrhy; B2B trhy; přímý prodej; produkt; cena; místo; propagace; lidé; partnerství; balení; programování; Marketing; marketing mix; analysis of general surroundings; SWOT analysis; Porter's model of five competitive forces; CANVAS model; marketing mix design; cooperation; fairs; B2B markets; direct sales; product; price; place; promotion; people; partnership; packaging; programming